(3cJGH GdCeQ HGdEJHGY hGdfgi Yf GdEHJOGYs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3EHQGgje Hf CMeO Hf jhSa GdfLOi GdJejei GdMfHdi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje Gddge Yhfc bGd Gddg JYGdi (B( (3hQMeJi hSYJ cd TF aSGcJHgG ddPjf jJbhf hjDJhf GdRcGI hGdPjf ge HBjGJfG jDefhf (B) s
(3BNQgG (B:s
(3gPg YbjOI Cgd GdSfI hGdLeGYI CMjGfG Gddg hCeGJfG YdjgG hLfHfG GdHOY eG XgQ efgG heG HWf Efg LhGO cQje hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs